PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE INSIDE OUTSIDE CIRCLE TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SEMESTER GENAP SMA NEGERI 3 METRO TAHUN PELAJARAN 2018/2019 - Adelia Putri Rahayu; Ningrum Ningrum; Tiara Anggia Dewi (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2021)
The Cooperative Learning model Inside Outside Circle is a learning strategy that allows students to exchange information at the same time and so that students can think critically and improve communication skills towards their learning outcomes, by applying the inside outside circle model in the classroom when the learning process will certainly make students produce meaningful knowledge.As for the problems in the research conducted by researchers, "There are still many students who have not experienced mastery learning in the economic learning outcomes of class X students of SMA 3 Metro in the academic year 2018/2019". From these problems, the formulation of the problem is "Is there an effect of Cooperative Learning learning type Inside Outside Circle on the economic learning outcomes of class X students of SMA Negeri 3 Metro academic year 2018/2019". The purpose of this study was to influence the use of the model of cooperative learning type inside outside circle on the economic learning outcomes of class X students of Negeri 3 Senior High School Metro tshun lesson 2018/2019. Then the hypothesis in this study are as follows: "There is an influence of the use of cooperative learning model type inside outside circle on the economic learning outcomes of class X students of SMA 3 Metro in the academic year 2018/2019". This type of research is a kind of pseudo research (Quasi Experimental), with an experimental design form that is the form of The Non-Equivalent Control Group Design. This design has a population of all classes X IPS 1, 2, 3, 4 with a total of 135 students. The experimental class is class X IPS 2 with a total of 32 students, and the control class is class X IPS 3 with a total of 35 students, the sampling method in this study is in the form of a Purposive Sample.Based on the results of the research conducted, the hypothesis is accepted, because the value of tcount> t table can be seen in the appendix list G, at a significance level of 5%, namely 3.18> 1.70. Students who are declared complete with KKM are (70) after being given treatment with the inside outside circle model which is as many as 28 students or with a percentage of 87.5% and those that are not complete are 4 students with a percentage of 12.5%. Thus it shows that the Cooperative Learning Model Type Inside Outside Circle has a positive influence on the economic learning outcomes of class X students of State High School 3 Metro Academic Year 2018/2019